Analysis of the Aesthetics of Contemporary Sculptures Suitable for Public Parks in Thailand - Booncham, Adool; Chantachon, Songkoon; Lao-Akka, Sastra (Thai Journal of East Asian Studies, 2018)
The purpose of this research was to examine the background, current conditions, problems and body of aesthetic knowledge of contemporary sculptures suitable for public parks in Thailand. The research area covered Bangkok, Chiang Mai, Phuket, Songkhla, Krabi and Ubon Ratchathani provinces in which there are constructions of contemporary sculpture permanently installed in the public parks. The research procedure used the qualitative research methodology. Data were collected from related literature and field studies using survey, interviews and focus group discussion from a group of 129 informants. The findings were presented by means of a descriptive analysis. The results show that there are 101 constructions of contemporary sculptures permanently installed in 15 parks across Thailand. The aesthetics of the contemporary sculptures in the public parks consists of 3 aspects: content, form and relationship with the environment and activities of the people who use the public parks.